2002
DOI: 10.1152/ajpgi.00491.2001
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 inhibits vasoactive intestinal peptide production by macrophages

Abstract: In schistosomiasis, eggs induce granulomas that have a vasoactive intestinal peptide (VIP) immunoregulatory circuit. This study explored the regulation of VIP production at sites of inflammation. Splenocytes from uninfected C57BL/6 mice expressed VIP mRNA and protein, which stopped following egg deposition. Eggs induce a Th2 response, suggesting that Th2 cytokines like interleukin (IL)-4 can regulate VIP. To address this issue, splenocytes from uninfected mice were incubated for 4 h with or without recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…We did not find VIP-ir or VIP gene expression in macrophages from lymphoid organs and peritoneal suspensions Delgado et al, 1996d), whereas Metwali et al (2002) described production of VIP by macrophages. Differences in state of cell activation or macrophage source could explain the discrepancy.…”
Section: Vasoactive Intestinal Peptide Production By Mastcontrasting
confidence: 72%
See 1 more Smart Citation
“…We did not find VIP-ir or VIP gene expression in macrophages from lymphoid organs and peritoneal suspensions Delgado et al, 1996d), whereas Metwali et al (2002) described production of VIP by macrophages. Differences in state of cell activation or macrophage source could explain the discrepancy.…”
Section: Vasoactive Intestinal Peptide Production By Mastcontrasting
confidence: 72%
“…On one hand, antigen-stimulated Th2 cells secrete VIP , which then promotes Th2 differentiation and survival, leading to more IL-4 production Delgado et al, 2002c). On the other hand, IL-4 inhibits constitutive VIP production by macrophages and reduces the levels of VPAC 2 receptors on Th2, but not Th1, cells (Metwali et al, 2000(Metwali et al, , 2002.…”
Section: Cd4 ϩ T Cell Function: Production Of Cytokines a Th1 Cytokmentioning
confidence: 99%
“…19,20 Flow cytometric analysis confirmed the adequacy of the separation (Ͼ95%). Purified macrophages were cultured in 0.6 ml of serum-free RPMI medium in 48-well flat-bottom plates at 37°C for 8 hours with IL-6 (Acris antibodies, Hiddenhausen, Germany), IL-10 (Acris antibodies), or TGF-␤1 (R&D systems) at the indicated concentrations.…”
Section: Macrophage Purification and Stimulationmentioning
confidence: 64%
“…Although PACAP expression in macrophages has not been described, studies concerning the expression of VIP (a close-related PACAP peptide) in macrophages have shown contradictory results. Some studies have been revealed the absence of the VIP expression in rat macrophages from lymphoid organs and in rat peritoneal macrophages [35,36], whereas, Metwalli and co-workers in 2002 reported the constitutively expression of VIP in splenic monocytes/macrophages subsets of healthy mice [37]. This inconsistency could be achieved to a dissimilar stage of activation or to the origin of the studied macrophages.…”
Section: Introductionmentioning
confidence: 99%